TRANSITIVITY AND DISCURSIVE RELEVANCE IN FEMINICIDE NEWS AND PROTEST SONGS ABOUT VIOLENCE AGAINST WOMEN (PERcursos Linguísticos, 2022)
This article analyzes, in the light of Functionalism in Linguistics, the phenomenon of Transitivity integrated into the news and protest song genres whose theme is violence against women, with the purpose of understanding how the components of Transitivity construct meanings in these linguistic environments. From a scalar and discursive conception of Transitivity (Hopper; Thompson, 1980; Thompson; Hopper, 2001; Silveira, 1990; author, 2020), the objective of this study is to correlate the results obtained with the application of the Transitivity parameters to the communicative purposes of the genres in question, in view of what is selected as Foregrounding (the most relevant information) and Backgrounding (the information that serves as a frame for the Foregrounding). The corpus of this research consists of six news about femicide published in online newspapers in Espírito Santo and four protest songs about violence against women. The results revealed that, in terms of discursive relevance, there is a significant difference between the news and protest song genres analyzed: while in the latter there was a predominance of events carried out from the perspective of female characters, in the former it was found that the narrative is built with a focus on the assassins (especially in terms of their modus operandi).